Entrepôt: Hubs, Scale, and Trade Costs - Sharat Ganapati; Woan Foong Wong; Oren Ziv (Center for Economic Studies and ifo Institute (CESifo), 2020)
Entrepôts are hubs that facilitate trade between various origins and destinations. We study the role these hubs, and the networks they form, play in international trade. Using novel data, we trace the paths of containerized goods entering the United States. We show that the majority of trade is indirect and sent through a small number of entrepôts, resulting in lower transport costs through scale economies by using larger ships. We build a model of endogenous entrepôt formation incorporating route choice by exporters within a Ricardian setting. We use the model to estimate trade costs on each shipping leg and develop a geography-based instrument to estimate a leg-level scale elasticity. Counterfactuals opening the Arctic Passage and Brexit quantify the effects of both network spillovers and scale economies. We find that spillovers from the transportation network doubles baseline welfare gains, with scale economies further tripling them.
Keywords: 330; trade costs; scale; hubs; transport costs; transportation networks; international trade; shipping